PWE-157 EUS Guided Trans-Gastric Pancreatic Pseudocyst Drainage- Does Standard Use of Fluoroscopy Just Complicate Things?. (17th August 2016) - Campbell, JA; Hopper, AD
Abstract : Introduction: Endoscopic pancreatic pseudocyst drainage is effective and associated with lower morbidity and mortality compared to surgical or percutaneous methods. EUS guidance is now the gold standard intervention due to a higher success rate and lower complication rate compared to blind puncture with fluoroscopic assistance. Many centres still use fluoroscopic guidance with EUS for all cyst-gastroscopy procedures. We present single centre experience of EUS guided pseudocyst drainage and complication rates comparing complication rates with and without fluoroscopic assistance. Methods: All EUS guided trans-gastric and trans-duodenal pseudocyst and acute pancreatic fluid collections drainage procedures from 2010 to January 2016 were included. Demographics, use of fluoroscopy and initial success of drainage with stent placement were recorded. All procedures were performed with midazolam and fentanyl sedation without endotracheal tube insertion. Standard trans-gastric drainage was attempted if there was good luminal/gastric wall apposition (cyst distance <10 mm) with no interposing vessels. Drainage was performed with 19 g needle puncture with fluid aspiration, 0.035 inch guide wire insertion, followed by 10 French cystotome puncture with 'endocut' effect 3 diathermy. A second wire was placed down the cystotome and subsequently, two 4cm 7 French double pigtail stents were placed over each wire. Balloon dilatation to 10 mm of the tract prior to stent placement was performed if the aspirated fluid was purulent or infection suspected. Success of drainage and immediate and delayed complications were identified from patient records. Complication rates were calculated separately for procedures performed with fluoroscopy and those without. The two groups were then compared (Fishers test). Results: 71 procedures were performed in 68 patients (mean age 50.8, SD 16.1). Immediate drainage was achieved in 69/71 (97.1%) of cases (2 procedures were abandoned due to bleeding). 2 procedures used fully covered metal stents, the remainder used two plastic stents. 2 procedures were performed via the duodenum due to cyst position. 9 patients experienced complications. Although the complications in the fluoroscopy group were more frequent there was no significant statistical difference in complication rates on comparing the two groups (p = 0.25). Conclusion: Although fluoroscopy could be helpful in certain circumstances, the routine additional use of fluoroscopy does not reduce complications for EUS guided trans-gastric drainage of pancreatic pseudocysts. Disclosure of Interest: None Declared